2007
DOI: 10.2106/jbjs.f.00222
|View full text |Cite
|
Sign up to set email alerts
|

Projections of Primary and Revision Hip and Knee Arthroplasty in the United States from 2005 to 2030

Abstract: These large projected increases in demand for total hip and knee arthroplasties provide a quantitative basis for future policy decisions related to the numbers of orthopaedic surgeons needed to perform these procedures and the deployment of appropriate resources to serve this need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
2,957
7
81

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,765 publications
(3,068 citation statements)
references
References 5 publications
23
2,957
7
81
Order By: Relevance
“…Subsequently a minimal (and negligible) increase in numbers performed per year was observed. This is in contrast with the expectation as published by Kurtz, since after the initial increase, we describe a stabilization in the incidence of THR in recent years 22, 23, 24. The increase in prevalence of patients with THR is most likely to be secondary to the increasing number of younger patients having surgery and the increasing life expectancy.…”
Section: Discussioncontrasting
confidence: 96%
“…Subsequently a minimal (and negligible) increase in numbers performed per year was observed. This is in contrast with the expectation as published by Kurtz, since after the initial increase, we describe a stabilization in the incidence of THR in recent years 22, 23, 24. The increase in prevalence of patients with THR is most likely to be secondary to the increasing number of younger patients having surgery and the increasing life expectancy.…”
Section: Discussioncontrasting
confidence: 96%
“…The growing demand for THA [16] coupled with age and increase in comorbidities of patients undergoing the procedure [12,13] warrants investigation of its current perioperative mortality rate. The primary focus of this paper was to determine overall mortality and causes of death at 30 and 90 days for patients undergoing THA.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging demographic and epidemiologic studies are projecting large increases in the demand for primary and revision arthroplasty over the next two decades [14][15][16]. Furthermore, THA is being performed in patients who are older and infirm [1,12,13,21,22,35,38,41].…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors have reported favorable outcomes after medial gastrocnemius flap coverage after TKA, with prosthesis retention rates as high as 82% to 92% [8,23,28], the largest English-language series to our knowledge included only 22 medial gastrocnemius flaps [6]. With an increasing number of patients undergoing TKA [14], the number of cases of periprosthetic joint infection also is increasing. Better understanding of outcomes after medial gastrocnemius flap coverage, including risk factors for treatment failure, will help to guide management of soft tissue defects in this setting.…”
Section: Introductionmentioning
confidence: 99%